Autoimmune and Neoplastic Thyroid Diseases Associated with Hepatitis C Chronic Infection - Poupak Fallahi; Silvia Martina Ferrari; Ugo Politti; Dilia Giuggioli; Clodoveo Ferri; Alessandro Antonelli (International Journal of Endocrinology)
Frequently, patients with hepatitis C virus (HCV) chronic infection have high levels of serum anti-thyroperoxidase and/or anti-thyroglobulin autoantibodies, ultrasonographic signs of chronic autoimmune thyroiditis, and subclinical hypothyroidism, in female gender versus healthy controls, or hepatitis B virus infected patients. In patients with “HCV-associated mixed cryoglobulinemia” (MC + HCV), a higher prevalence of thyroid autoimmune disorders was shown not only compared to controls, but also versus HCV patients without cryoglobulinemia. Patients with MC + HCV or HCV chronic infection show a higher prevalence of papillary thyroid cancer than controls, in particular in patients with autoimmune thyroiditis. Patients with HCV chronic infection, or with MC + HCV, in presence of autoimmune thyroiditis, show higher serum levels of T-helper (Th)1 (C-X-C motif) ligand 10 (CXCL10) chemokine, but normal levels of Th2 (C-C motif) ligand 2 chemokine, than patients without thyroiditis. HCV thyroid infection could act by upregulating CXCL10 gene expression and secretion in thyrocytes recruiting Th1 lymphocytes that secrete interferon-γ and tumor necrosis factor-α. These cytokines might induce a further CXCL10 secretion by thyrocytes, thus perpetuating the immune cascade, which may lead to the appearance of autoimmune thyroid disorders in genetically predisposed subjects. A careful monitoring of thyroid function, particularly where nodules occur, is recommended in HCV patients.